Impact of color and anti-hail net installation system on microclimate and leaf water status in Vitis vinífera L. cv. Malbec in Mendoza, Argentina - Nahuel, Cesar Gabriel; Castro, Pablo; Gimenez, Víctor Germán; Osorio, Horacio Ruben; Lazaro, Hilario Javier; Gomez, Aldo Hector; Nahuel, Edgardo Daniel; Vico, Alexandra Melanie; Luna, Ana Belen; Carbajal Ramos, Irene; Prieto, Jorge Alejandro (Sociedad Argentina de Fisiología Vegetal, 2025)
Poster